Customer knowledge management in the insurance industry in Malaysia. The role of knowledge sharing, market and technology turbulence / Ahmad Suffian Mohd Zahari - Mohd Zahari, Ahmad Suffian (Institute of Graduate Studies, UiTM, 2014)
Customer Knowledge Management (CKM) is derived from the knowledge management concept, which can be applied by organizations strategies to satisfy their customers’ needs and wants. The dimensions of customer knowledge management are developed from the knowledge flow perspectives such as knowledge for customers, knowledge about customers and knowledge from customers. In this manner, CKM refers to the management of knowledge for customers, knowledge about customers and knowledge from customers to improve organizational performance. This study examined the effects of CKM dimensions in influencing organizational performance in insurance industry in Malaysia. This study also investigated the influence of moderating effects of market and technology turbulence in the relationship between knowledge sharing and organizational performance and between CKM and organizational performance. This study also examined the mediating effects of knowledge sharing in the relationship between CKM and organizational performance. A total of 180 managers from various insurance companies in Malaysia are involved in this study by voluntarily completing the survey questionnaires.